PENGARUH PENGUNGKAPAN INTELLECTUAL CAPITAL TERHADAP COST OF EQUITY CAPITAL PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA PERIODE 2010-2012 - Didik Setiawan, 11.05.52.0078; ., Sunarto (Students Journal of Accounting and Banking, 2015)
This study aims to analyze the effect of intellectual capital disclosures are reported to the companys annual cost of equity capital. Intellectual capital disclosure are tested per component of human capital and structure capital. In this research equity capital is measured by multiple- rate dividend growth model that has been modified, whereas to measure intellectual capital disclosures using index Li et al. (2008). This study using purposive sampling method resulting in 99 samples of companies listed on the Indonesian Stock Exchange (BEI) in the period 2010-2012. The research proves that the intellectual capital disclosure both human capital and the structure capital is not shown to have a relationship to the cost of equity. This of intellectual capital disclosure can not lower the cost of equity.Keywords: Intellectual Capital Disclosures, Human Capital, Structure Capital, Cost of Equity Capital